IMPROVING STUDENTS’ VOCABULARY MASTERY BY USING ANIMATED VIDEO - Chandra Andrean; Sofian Sofian; Yanti Sri Rezeki (Universitas Tanjungpura, 2019)
AbstractThe research was conducted in order to solve the students’ problem in mastering vocabulary. The form of the research is classroom action research, in which the subjects are seventh-grade students of SMP Negeri 13 Pontianak in Academic Year 2018/2019. The subject of this research were 25 students in VII J. The data were collected using field note, interview, and test. The result of data analysis showed the improvement of students’ vocabulary mastery. By using animated video in teaching and learning process, the students’ mean score improved from 64,4 to 80,4 in the last cycle. The video made the students enjoy the learning process. Two elements provided in the video, visual and sound, made students easier in recognizing the vocabulary. The students’ knowledge in vocabulary also improved from cycle to cycle. It also helped students in answering the test. It can be concluded that the students’ vocabulary mastery by using animated video was improved. In other words, the video helped students in memorizing the words and improved their vocabulary.Keywords: Animated Video, Improving, Vocabulary.